IMPLIKASI FOREIGN DIRECT INVESTMENT SINGAPURA DI INDONESIA TERHADAP PENGEMBANGAN KAWASAN INDUSTRI (STUDI KASUS: PT KAWASAN INDUSTRI KENDAL) - Rahayu Efendi; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indonesia as a newly industrialized country continues to experience moderate levels of economic growth. Indonesia has good relations with Singapore, the two countries agreed to strengthen cooperation in thr three priority sectors, namely the capital market, digital economy and tourism as well as other supporting infrastructure. Meanwhile, Singapore has become the main source of foreign direct investment in Indonesia in the last five years. Singapore established a multi-billion dollars investment company in Indonesia which is a joint venture between PT Jababeka Tbk and Sembcorp Development Ltd. The joint venture company, PT Kawasan Industri Kendal, Indonesia.This study uses an analysis of the nation-state level in which the state is the main actor. To solve the problem, the researcher uses the perspective of neoliberalism which explains that investment is an important factor in improving the country’s economy. Under the descriptive qualitative method, the researcher found the problem solver based on the data that collected from books, journals, articles, websites and some legal documentary related to the research. This research is in Kendal district with a time from 2016 to 2019.This study also proves that the implications of Singapore's foreign direct investment in Indonesia through PT Kendal Industrial Park have many positive effects. The Kendal Industrial Park is proven to be able to increase the absorption of local labors, improve the quality of human resources and increase regional economic growth. In addition, the industrial estate continues to carry out construction and will complete phase one. The government is expected to be more active in promoting industrial estates to attract investors. Keywords: Foreign Direct Investment, Kendal Industrial Park, Economic Growth